DETERMINATION OF POLYCHLORINATED BIPHENYLS (PCBS) LEVELS IN THE SOIL AND WATER FROM ELECTRONIC WASTE DUMPSITE AT ALABA, LAGOS STATE, NIGERIA - Ayoola, Ebenezer O.; Enwemiwe, Victor N.; Oluwagbemi, Emmanuel B.; Obi, Clement C.; Okushemiya, John U.; Ufoegbune, Hilda; Egwenum, Judith (FUDMA Journal of Sciences, 2023)
Polychlorinated biphenyls (PCBs) may occur in the environment at high levels capable of threating human health. PCB levels in the water and soil of electronic waste dumpsite in Alaba, Lagos was evaluated to capture the public health status. Six (6) samples comprised of three (3) water and soil samples were randomly collected. The soil and water samples were extracted using USEPA methods and analyzed with Gas Chromatography Electron Capture Detector (GC-ECD) for detection of PCBs. Results show that nineteen (19) PCBs congeners were present in both water and soil samples including PCB – 1, 5, 18, 31, 44, 52, 66, 87, 101, 110, 138, 141, 151, 153, 170, 180, 183, 187 and 206. PCB-1 was highest (2.28 ± 1.85 µg/L) and PCB-206 (0.01 ± 0.02 µg/L) lowest in water samples. PCB level in water samples exceeded the tolerable levels for PCBs in portal water systems (0.5 µg/L). The concentration of PCB -44 in soil samples was highest (6.36 mg/kg) and PCB-180 was lowest (0.00 mg/kg). The differences between PCB levels in soil and water were not significant (p>0.05). Hazard index for the water sample for adults and children was greater than 1 showing no carcinogenic effects. Cumulative cancer risk due to PCBs in water was below 1.0 x 10-4 and shows no cancer risk. Therefore, electronic waste deposition and PCB levels in soil and the water in this location should be regularly checked in order to avoid the disruption of endocrine system in aquatic organisms and wildlife.
Keywords: Polychlorinated biphenyls; electronic waste dumpsite; cancer risk